2022
DOI: 10.1021/acsagscitech.2c00030
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial Inoculation Enhances Nutrient Use Efficiency and Grain Quality of Basmati Rice in the System of Rice Intensification

Abstract: Field experiments were carried out to evaluate the influence of the system of rice intensification (SRI) and microbial inoculation, which revealed significant enhancement in the uptake of nitrogen and zinc in brown rice grain, husk, and straw. Increases of 30−60% in the soil dehydrogenase activity and the total polysaccharide content were recorded with an Anabaena-Mesorhizobium biofilm, while the N recovery efficiency was the highest (86%) with BF1−4 (cyanobacterial consortium) inoculant. Available N and zinc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In the rice intensification system (SRI) with microbial inoculation ( Anabaena –Trichoderma viride and Anabaema – Mesorhizobium sp.) contributes significantly to the increase in nitrogen and zinc absorption in Basmati rice grains and higher productivity indexes, also illustrating the benefits of a cyanobacterial consortium . In another study with grain culture and coinoculation, it was reported that the use of a microbial inoculant composed of photosynthetic cyanobacteria (Anabaema cylindrica and Nostoc muscorum) and A.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In the rice intensification system (SRI) with microbial inoculation ( Anabaena –Trichoderma viride and Anabaema – Mesorhizobium sp.) contributes significantly to the increase in nitrogen and zinc absorption in Basmati rice grains and higher productivity indexes, also illustrating the benefits of a cyanobacterial consortium . In another study with grain culture and coinoculation, it was reported that the use of a microbial inoculant composed of photosynthetic cyanobacteria (Anabaema cylindrica and Nostoc muscorum) and A.…”
Section: Discussionmentioning
confidence: 92%
“…contributes significantly to the increase in nitrogen and zinc absorption in Basmati rice grains and higher productivity indexes, also illustrating the benefits of a cyanobacterial consortium. 40 In another study with grain culture and coinoculation, it was reported that the use of a microbial inoculant composed of photosynthetic cyanobacteria (Anabaema cylindrica and Nostoc muscorum) and A. brasilense, combined with nitrogen fertilization, favored maize production components. 41 In summary, we demonstrated that A. brasilense (strain Ab-V6) + P. fluorescens (strain CCTB03) combined with 70 and 90 kg of N ha −1 in coverage promoted average increases of 30 and 38.5%, respectively, in rice production using ST technology.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, cyanobacteria-based biofilm inoculants were found to be more effective under SRI crop management than under conventional rice management for increasing the concentrations of zinc, copper, iron, and manganese measurable in the rice grain. Also, there was a significant increase in the activity of defense-related and pathogenesis-related enzymes, as well as in the yield parameters of rice plants (Adak et al, 2016;Shivay et al, 2022). Aerobic and organic soil conditions under SRI also favor greater root growth and increased nutrient acquisition by organicallyfertilized rice plants, with reduced accumulation of toxic elements in the soil such as Fe 2+ and Mn 2+ (Turmel et al, 2011).…”
Section: The Diverse and Dynamic Structure Of Microbial Communities U...mentioning
confidence: 98%
“…Cyanobacteria are known to produce sugars, amino acids, auxins, vitamins, and phytohormones, which helps in stimulating plant growth ( Karthikeyan et al., 2007 , Misra and Kaushik, 1989 , Obana et al., 2007 , Rastogi and Sinha, 2009 ). In agriculture, cyanobacteria and cyanobacteria- based formulations are known to have several benefits as they improve soil stability ( Peng and Bruns, 2019 ; Prasanna et al., 2021a ), fix atmospheric nitrogen ( Pereira et al., 2009 , Singh, 1961 , Venkataraman, 1972 ), provide protection against pests and diseases ( Bao et al., 2021 , Mahawar et al., 2020 , Wiegand and Pflugmacher, 2005 ) , play an important role in the alleviation of salinity and drought ( Sneha et al., 2021 ) and biofortification of plant parts, including produce ( Nishanth et al., 2021a ; Rana et al., 2012 ; Shivay et al., 2022 ). As biofertilizers, they play a critical role in improving the availability of macro- and micronutrients, besides enriching soil carbon through photosynthesis.…”
Section: Introductionmentioning
confidence: 99%